2018
DOI: 10.1371/journal.pone.0199795
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multi-facetted blended eHealth intervention during intake supporting patients and clinicians in Shared Decision Making: A cluster randomised controlled trial in a specialist mental health outpatient setting

Abstract: ObjectiveTo investigate the effectiveness of a multi-facetted blended eHealth intervention, called SDM-Digital Intake (SDM-DI), in which patients and clinicians are supported in Shared Decision Making during the intake process.MethodsThe study is a two-arm matched-paired cluster Randomised Controlled Trial in a specialist mental health outpatient setting with two conditions: SDM-DI and Intake As Usual (IAU). Four intake teams were allocated to each arm. All patients who followed an intake, were asked to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Although this could have influenced our results, research shows that to this date, SDM is still not widely implemented in mental health care . Furthermore, recent literature shows that the difficulties we identified regarding the implementation of SDM in clinical practice seem similar across different patient groups and health care settings . This suggests that despite SDM developments in recent years, our findings are still relevant, and our conclusions may be applicable in a wider range of health care area's in the Netherlands and internationally.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Although this could have influenced our results, research shows that to this date, SDM is still not widely implemented in mental health care . Furthermore, recent literature shows that the difficulties we identified regarding the implementation of SDM in clinical practice seem similar across different patient groups and health care settings . This suggests that despite SDM developments in recent years, our findings are still relevant, and our conclusions may be applicable in a wider range of health care area's in the Netherlands and internationally.…”
Section: Discussionmentioning
confidence: 73%
“…Yet effects on SDM and health service outcomes remain inconclusive, and SDM is not yet widely implemented across mental health care settings . Some authors suggested that the effects of decision aids are weak, because of a less than optimal uptake of interventions/tools in current clinical practice, and that incentives might be needed to stimulate SDM and the use of DAs and other SDM interventions . In addition, Metz et al found an effect only for mood disorders and not for other diagnoses, suggesting that their SDM intervention might have been too generic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations